THE ROLE OF EMPATHY IN THE FORMATION OF INTERPERSONAL RELATIONSHIPS - Shutiak, Irina; Fedortchouk, V.V. (SWorld-Ger Conference proceedings, 2024)
This research paper examines the role and importance of empathy in understanding and supporting interpersonal relationships. It explores the key aspects of empathy, its impact on communication, and its role in conflict resolution. The paper notes that emp